2016
DOI: 10.1667/rr14267.1
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Microgravity and Low-Dose/Low-Dose-Rate Radiation Induces Oxidative Damage in the Mouse Brain

Abstract: Microgravity and radiation are stressors unique to the spaceflight environment that can have an impact on the central nervous system (CNS). These stressors could potentially lead to significant health risks to astronauts, both acutely during the course of a mission or chronically, leading to long-term, post-mission decrements in quality of life. The CNS is sensitive to oxidative injury due to high concentrations of oxidizable, unsaturated lipids and low levels of antioxidant defenses. The purpose of this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 52 publications
(54 reference statements)
3
51
0
Order By: Relevance
“…Similarily, a dose-dependent loss of neurons is noticed when looking at both neurogenesis and cellular differentiation of neurons in the hippocampal region of the brain [5]. Also, a study looking at the oxidative damage of brain tissue after a prolonged exposure (21 days before brain tissue isolation) of low-dose (0.04 Gy) radiation exposure observed an increase in oxidative stress biomarkers that could possibly lead to brain injury [6]. In contrast, a more recent histological study has shown that tissue integrity or neuron distribution was not changed a year after irradiation of 45 Gy delivered with 5 Gy fractions twice per week for 4.5 weeks [7].…”
Section: Introductionmentioning
confidence: 82%
“…Similarily, a dose-dependent loss of neurons is noticed when looking at both neurogenesis and cellular differentiation of neurons in the hippocampal region of the brain [5]. Also, a study looking at the oxidative damage of brain tissue after a prolonged exposure (21 days before brain tissue isolation) of low-dose (0.04 Gy) radiation exposure observed an increase in oxidative stress biomarkers that could possibly lead to brain injury [6]. In contrast, a more recent histological study has shown that tissue integrity or neuron distribution was not changed a year after irradiation of 45 Gy delivered with 5 Gy fractions twice per week for 4.5 weeks [7].…”
Section: Introductionmentioning
confidence: 82%
“…29 Similarly, low-dose γ irradiation is capable of upregulating NADPH oxidase in central nervous system in mice. 30 Increased NADPH oxidase expression is possible sources of increased ROS production mirrored by an increase in DNA damage. Further investigation on the NOX’s activities in endogenous ROS production will help to clarify the additive effects of radiation-induced DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…All mice were handled and sacrificed by our co-author, XW Mao, at Loma Linda University under AUP 8130028 in a previous study [31]. All data were obtained from cardiac tissue samples collected from that previous study.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, increased oxidative stress coupled with impairment of antioxidant mechanisms and inflammation have been shown in skeletal muscle following exposure to simulated microgravity [30]. Recently, Mao et al showed that a combined exposure to hindlimb unloading (HU) and low-dose rate γ-radiation may increase oxidative damage and decrease antioxidant protein content in the mouse brain [31]. To be able to model simultaneous HU and exposure to low-dose rate ionizing radiation, Mao et al placed cages of hind-limb unloaded mice onto Co-57 plates that emitted ionizing radiation in the form of γ-rays at an average dose rate of 0.01 cGy/h.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation